Factors influencing customers loyalty towards Islamic Banking: a case study in Gombak, Selangor / Farhan Luqman Rahman - Rahman, Farhan Luqman (Faculty of Business and Management, 2019)
The banking system which is based on the principles of Islamic Shariah law that is known as Islamic banking system. For principles, it has two basic that govern Islamic banking which are mutual sharing of profit and loss and the prohibition of the collection and payment of interest. Under Islamic law, it is not permitted the activities that involved interest, gambling and speculative. These basic principles are important when the establishment of an Islamic bank. The main objective of this study is to examine the factors that influence customer loyalty towards Islamic banking. The independent variables included Shariah compliant, product quality, service quality, and convenience. This research is based on data obtained from questionnaires which 300 respondents from Gombak, Selangor. The data collection method is using structured questionnaire and were personally administrated. The study's limitation relates to generalization of result and time constraints. This study is significantly important for the academic point of view, as well as for the bankers to find out the design and motif of customer loyalty for Islamic banks.